Life of a Personality in the Space of Spirituality - Ivan Beh (Pedagogical Discourse, 2012)
The article reveals the interpersonal interactions that occur in a particular social group that directly affect the life of each member. This dependence is peculiar to both small spontaneous and non-contact formal associations that reflect the general structure of society. A small informal group will be more effective in this regard. Until now, group processes of value-meaning harmonization or confrontation have been traced at both theoretical and applied levels only in the context of forming a single socially important motivational basis for the functioning of a group and its progressive development. Here, preference was given to the category of value cohesion and the content of interpersonal contacts that arose under its influence.